Family Education in Increasing Exclusive Breastfeeding Coverage In Lakarsantri District Surabaya - Pratami, Evi; S, Rekawati; Isfentiani, Dina; Sukesi, Sukesi; Kasiati, Kasiati; Purwanti, Dwi; Evi Yunita Nugrahini; Pipitcahyani, Tatarini Ika; Titi Maharrani; Novita Eka Kusuma Wardhani (Frontiers in Community Service and Empowerment, 2025)
Breast milk is the best food for babies and always disseminated by the government and health workers. Regulations explains that every baby has the right to get exclusive breast milk from birth for 6 (six) months. There are 34.64% of mothers in Lakarsantri Subdistrict, Surabaya who do not provide exclusive breastfeeding to their babies. There are many reasons given, including breast milk does not come out, the baby does not want to breastfeed and the mother works. Community service activities in the form of education on exclusive breastfeeding mothers and families. This community service activity aims to increase the commitment of mothers and families in exclusive breastfeeding. The counseling material includes the definition of exclusive breastfeeding, how to breastfeed, how to store breast milk properly and efforts to increase breast milk production. The participants were mothers and families with infants and toddlers. The number of participants was around 20 people. The media used were leaflets and demonstrations on how to pump breast milk. The results of the activity were able to increase the community's knowledge of the definition, how to store breast milk, factors that affect breast milk and the correct way to express breast milk.